Two new species of Parasesarma De Man, 1895, from Southeast Asia (Crustacea: Decapoda: Brachyura: Sesarmidae) - Rahayu, Dwi Listyo; Ng, Peter K.l. (Zootaxa, 2009)
Two new species of sesarmid crabs of the genus Parasesarma De Man, 1895, are described from mangrove forests in Southeast Asia. Parasesarma paucitorum n. sp. is described from northern Sulawesi and is allied to P. leptosoma (Hilgendorf, 1869) but differs from the latter in the form of its carapace, leg proportions, the structure of the tubercles on the cheliped dactylus, and the male first pleopods. Parasesarma raouli n. sp. is described from southern Peninsular Malaysia and is differentiated from the allied P. charis Rahayu & Ng, 2005, and P. anambas Yeo, Rahayu & Ng, 2004, by the number and form of the tubercles on the cheliped dacylus, the shape of the male abdomen and structure of the male first pleopods.